2018
DOI: 10.1037/neu0000480
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal face and voice recognition disorders in a case with unilateral right anterior temporal lobe atrophy.

Abstract: the present case report seems to show that a unilateral right ATL atrophy can lead to a multimodal people recognition disorder through face and voice, in the absence of recognition difficulties through personal name. (PsycINFO Database Record (c) 2018 APA, all rights reserved).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…You might be talking to your friend about their holidays one minute and then their new job the next, but of course their identity does not change across the shift in context. This point is clearly seen in case studies of neuropsychological deficits involving structural damage to anterior temporal lobes, which point strongly to the existence of modality-independent forms of loss of memory for people in which severe deficits affect the retrieval of identity-specific information about a familiar individual from their face, voice, and even their name Young, Frühholz and Schweinberger (cont'd) 11 [26,27,48,49,73,74]. The same underlying functional architecture is evident in widely-used functional models [11,[75][76][77][78].…”
Section: Functional Demands Of Face and Voice Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…You might be talking to your friend about their holidays one minute and then their new job the next, but of course their identity does not change across the shift in context. This point is clearly seen in case studies of neuropsychological deficits involving structural damage to anterior temporal lobes, which point strongly to the existence of modality-independent forms of loss of memory for people in which severe deficits affect the retrieval of identity-specific information about a familiar individual from their face, voice, and even their name Young, Frühholz and Schweinberger (cont'd) 11 [26,27,48,49,73,74]. The same underlying functional architecture is evident in widely-used functional models [11,[75][76][77][78].…”
Section: Functional Demands Of Face and Voice Recognitionmentioning
confidence: 99%
“…Other regions show responses to both faces and voices (yellow highlighting), thus forming candidates for integrating vocal and facial signals involving speech, affect or identity [3,8,[22][23][24][25]. Regions likely to also have relatively post-perceptual responses are highlighted in blue [19,23,[26][27].…”
Section: Box 2: Brain Regions Involved In Face and Voice Perceptionmentioning
confidence: 99%
“…Consistent with these studies, group studies of SD patients have shown that the recognition of famous names is relatively more affected by a left anterior temporal atrophy, while famous face recognition deficits are relatively more affected by a right anterior temporal atrophy [11,33,34]. Neuropsychological single-case studies of patients with anterior temporal atrophy [35][36][37][38] or focal anterior temporal damage [39] have also found evidence for graded hemispheric dissociations within person-related recognition abilities, i.e., relative differential impairments in accessing person-related information from faces or names depending on the hemispheric side of the lesion. Moreover, the lack of crossmodal adaptation effects to sequences of faces and names with the same identity in functional magnetic resonance imaging (fMRI) [40] has reinforced this view of two separate processing pathways for faces and names in the human brain.…”
Section: Introductionmentioning
confidence: 63%
“…At the same time, multimodal deficits in recognizing people from both faces and voices have also been reported. Such multimodal deficits have been variably interpreted as potentially being caused by unilateral right-hemispheric anterior temporal lesions [ 89 , 90 , 91 ], or as being related to bilateral lesions [ 88 , 92 ]. In the present study, the N250 and sustained activity for learned vs. novel voices in the test phase did not exhibit significant lateralization to the right hemisphere.…”
Section: Discussionmentioning
confidence: 99%